Celebrating Europe An Asian Journey - Asad Latif (Institute of Southeast Asian Studies, 2012)
Europe's mythical origins lie in Zeus' abduction of the Asian princess Europa. Down the real centuries, Asia has played a crucial role in the making of Europe - as an object of Orientalist fantasy and colonial desire, but also of the spread of the liberating values and humane letters associated with the continent. In this book, a lifelong admirer of Europe casts a critical yet loving eye on the continent to ask what it means to him. The book revolves around a series of personal encounters. These range from following his father to Cambridge, and meeting two Bengali lovers in Calcutta who cherish Eros with classical Greek purity, to watching his wife recover in a Polish hospital that lavishes care on her for almost free. These encounters are intertwined with passionately argued essays on the Holocaust, the Soviet ideal and the Berlin Wall as keenly-contested sites of the European imagination. A chapter on Giuseppe Tomasi di Lampedusa's historical novel, The Leopard, combines literary and political analysis to peer into the heart of Italy, while an essay on champagne in France discovers the France in champagne. An analysis of secularism in the post-9/11 world defends one of the abiding legacies of Europe. Finally, a chapter on postmodern Europe upholds the European Union as perhaps the most exciting international project on offer today. The literary flair of this scholarly book captures the vividness of the intellectual engagement between Asia and Europe